Market price forecasting and profitability – how to tame mrandom walk? - Stádník, Bohumil (Business: Theory and Practice, 2013)
Directional forecasting of a future market price development of liquid investment instruments is the focus of interest of investment companies, individual investors, banks and other financial market participants. This problematic has still not been fully answered because the market price development is a process which is very close to a random walk and appropriate models are still under the discussion. The opportunities can be used for the better prediction, their usage for profit making, quantification and also their discussion according to the current financial market models (models with the direction or the volatility dependence) is the core of the paper. The purpose of this research is also to simplify the whole situation for the practitioners due to the complicated theoretical background of this financial market topic.